2021
DOI: 10.1002/ccr3.5183
|View full text |Cite
|
Sign up to set email alerts
|

Pyelonephritis‐associated Staphylococcus saprophyticus bacteremia in an immunocompetent host: Case report and review of the literature

Abstract: Staphylococcus saprophyticus is a gram-positive, novobiocinresistant, coagulase-negative staphylococcus species. 1 It is the second most frequent causative microorganism in acute uncomplicated urinary tract infections in young, sexually active women. 2 However, it can present with a variety of complicated genitourinary tract infections which include prostatitis, pyelonephritis, and epididymitis. 3 Staphylococcus saprophyticus bacteremia rarely complicates the involvement of the urinary tract, particularly in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
2
3
0
Order By: Relevance
“…However, more serious liver lesions were observed in mice than that in the armadillos, which may be related to differential effect of the bacterium based on species. Moreover, high bacterial load, tubular epithelial cells necrosis, and in ammatory cell in ltration was found in kidneys of the mice infected with S. saprophyticus, which is in agreement with the kidney lesions reported in humans (Matarneh et al 2021). A previous study reported S. saprophyticus can locate in the kidneys of a urease-induced UTI rat model that exhibited in ammation in the kidneys (Gatermann et al 1989;Kline et al 2010;Matarneh et al 2021).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, more serious liver lesions were observed in mice than that in the armadillos, which may be related to differential effect of the bacterium based on species. Moreover, high bacterial load, tubular epithelial cells necrosis, and in ammatory cell in ltration was found in kidneys of the mice infected with S. saprophyticus, which is in agreement with the kidney lesions reported in humans (Matarneh et al 2021). A previous study reported S. saprophyticus can locate in the kidneys of a urease-induced UTI rat model that exhibited in ammation in the kidneys (Gatermann et al 1989;Kline et al 2010;Matarneh et al 2021).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, high bacterial load, tubular epithelial cells necrosis, and in ammatory cell in ltration was found in kidneys of the mice infected with S. saprophyticus, which is in agreement with the kidney lesions reported in humans (Matarneh et al 2021). A previous study reported S. saprophyticus can locate in the kidneys of a urease-induced UTI rat model that exhibited in ammation in the kidneys (Gatermann et al 1989;Kline et al 2010;Matarneh et al 2021). Altogether, these ndings suggest that S. saprophyticus probably infection in two armadillos, but the detailed mechanism needs to be further unmasked.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To date, S. saprophyticus has been reported as the second most frequent causative organism of uncomplicated UTIs in women ( 2 ). Infrequently, it is also responsible for several complications including acute pyelonephritis ( 3 , 4 ), bloodstream infection ( 5 ), endocarditis ( 6 ), and nephrolithiasis ( 7 ). In terms of body habitats, S. saprophyticus is present in humans as part of the normal microbiota of the skin and mucosal surfaces in perineum, rectum, urethra, cervix, and gastrointestinal tract ( 2 , 8 ).…”
Section: Introductionmentioning
confidence: 99%